The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2147/opth.s40762
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional LASIK flap thickness variability: topographic central, paracentral and peripheral assessment, in flaps created by a mechanical microkeratome (M2) and two different femtosecond lasers (FS60 and FS200)

Abstract: Video abstract Video

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 34 publications
3
27
1
Order By: Relevance
“…This demonstrated that the thicker corneas were associated with the thicker flaps and the thinner corneas with thinner flaps. Similar results were also reported in previous studies 8,16,24,28,29. We found no correlation between other parameters.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This demonstrated that the thicker corneas were associated with the thicker flaps and the thinner corneas with thinner flaps. Similar results were also reported in previous studies 8,16,24,28,29. We found no correlation between other parameters.…”
Section: Discussionsupporting
confidence: 93%
“…The flap thickness created with different microkeratomes has been shown to be different from the intended values 15–29. In this study, the Moria M2 single-use 90 microkeratome, designed to achieve a corneal thickness of 120 µm was used in all eyes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Creation of a LASIK flap with a femtosecond laser is considered advantageous to microceratome7,8 for a more centered, higher controlled-geometry, both in depth9 as well as diameter 10. In an earlier effort to validate the precision and accuracy of flap creation, we had introduced a quantitative digital analysis technique for accurate measurement of flap diameter and extent of OBL for flaps created using the Alcon/WaveLight FS200 femtosecond laser during LASIK and prior to lifting of the flap 10…”
Section: Discussionmentioning
confidence: 99%
“…13 However, the advent of femtosecond lasers definetively enhanced the accuracy, by reducing the standard deviation for flap thickness, as well as improving geometry of the lamellar cut. [13][14][15][16][17] Every surgeon should be alert about such complication and be aware about the standard deviation of the thickness of the flap from the instrumentation he or she has available.…”
Section: Discussionmentioning
confidence: 99%